Isolation and Characterization of MYB-Related Genes from Oil Palm (Elaeis Guineensis Jacq.) - Teoh, Wan Chin (2002)
Myb is a sequence specific DNA-binding protein that can activate or inactivate promoters containing its binding site. Plant Myb proteins represent a group of transcription factors which have a DNA-binding domain similar to that found in the products of the animal myb proto-oncogenes. Some of the functions, which have so far been assigned to plant myb genes, include regulation of phenylpropanoid biosynthesis, control of cellular differentiation, and contribution to control of plant responses to hormones and various stresses. Two different myb-like genes were isolated. OpMyb24, which contains a full-length coding region, was obtained from an oil palm zygotic embryo (OPZE) cDNA library. Its Myb-domain shows extensive homology to the snapdragon proteins Myb308 and Myb330, and maize protein Zm3 8, and these myb-like genes have been found to be involved in regulating phenylpropanoid and lignin biosynthesis, and control of flavonoid biosynthesis. The second myb-like gene was isolated from oil palm suspension culture (OPSe) cDNA library, OpMyb15, which lacks the 5' end, has greater similarity to MIXT A of Antirrhinum, which is essential for the development of the conical form of petal epidermal cells. These two predicted gene products showed high similarity within the myb domain with other Myb genes from other species; however, outside of this region virtually no similarity was found. Expression of OpMyb24 and OpMyb15 was detected in all tissues tested, except OpMyb24 transcript, which was not detected in three-month-old and young leaves. Both OpMybs were relatively more abundant in 28-cm male flowers and meristems, which showed distinct, tissue-specific expression patterns. For the expression study in treated oil palm in vitro seedlings, OpMyb15 and OpMyb24 transcripts accumulated to high levels in response to gibberellic acids, while the levels of OpMyb24 decreased significantly after wounding or heavy metals treatment. At the same time, OpMyb24 mRNA increased slightly after UV light exposure. Much remains to be learned about the function of these oil palm Myb genes in their molecular responses in GA-regulated processes, wounding, heavy metal treatment and UV light exposure. From the Southern blot analyses, these two OpMybs were determined to exist as a small gene family. As overexpression or downregulation of a gene is most frequently achieved by the production of transgenic plants carrying sense or antisense copy of the gene, the coding sequence of OpMyb24 was successfully inserted in both sense and antisense orientations between the 3 5 S CaMV promoter and nos terminator of the expression vector p35S/NOS. The both constructs were consequently subc10ned into a binary vector (pCAMBIA 130 1) to be used to transform oil palm in the future. This is one of the approaches may provide important clues about the function of OpMyb24 by studying the phenotype of the resulting transgenic oil palm.